This I Believe - Adler, Irene R. (Tufts Archival Research Center, 2006)
Irene Adler, Senior in the College of Home Economic at Cornell University, discusses the importance of faith in her personal life and in society and explains why it gives her self-confidence to succeed and also why it enables people to work together in society.